2014
DOI: 10.1590/0103-6440201302356
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Successful Root Canal Treatment

Abstract: Knowing the outcome of root canal treatment (RCT) is determinant to substantiate the clinical decision making process, especially when RCT is weighed against the extraction of natural teeth or replacement by prosthetic elements. The ideal scenario in all clinical situations should combine healing/prevention of disease (apical periodontitis) and the functional retention of the tooth. Understanding the risk factors associated with endodontic failure is a key factor to increase the chances of success. The logical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
191
0
40

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 251 publications
(270 citation statements)
references
References 78 publications
2
191
0
40
Order By: Relevance
“…Several studies have considered sodium hypochlorite as the substance that agglutinates the largest number of characteristics for its use as irrigant in infected root canals [4,5,8,9]. Bhardwaj et al [34] reported that passive ultrasonic irrigation with1% sodium hypochlorite was effective to completely remove E. faecalis biofilms compared to natural substances (Aloe Vera, Nona juice and propolis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have considered sodium hypochlorite as the substance that agglutinates the largest number of characteristics for its use as irrigant in infected root canals [4,5,8,9]. Bhardwaj et al [34] reported that passive ultrasonic irrigation with1% sodium hypochlorite was effective to completely remove E. faecalis biofilms compared to natural substances (Aloe Vera, Nona juice and propolis).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial growth is enhanced by complex anatomy of root canal system, inaccessible areas to endodontic instruments, which represent an ideal environment for bacterial biofilm structuring [2,3]. Bacterial biofilm is structured from microorganisms attachment on a solid surface embedded in an extracellular matrix, resistant to antimicrobial agents, what favors the maintenance of infection process and represents a special challenge for successful root canal treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the presence of high rates of success in endodontic therapy, mainly due to knowledge of internal dental anatomy and advancements in science and technology, failures in root canal treatment have been described [7]. Once diagnosed as a failure of primary endodontic therapy, the tooth may be submitted to a new intervention, which is the usual procedure in endodontics in order to correct the failures of the previous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several instrumentation techniques, with different kinematics and types of instruments, have been introduced into the market with this goal in mind. 2,3 Traditional stainless steel files and nickel-titanium (NiTi) files used in rotary and reciprocating systems are universally employed.…”
Section: Introductionmentioning
confidence: 99%